AKSESIBILITAS MASYARAKAT MISKIN DALAM MEMPEROLEH PELAYANAN KESEHATAN (Studi Kasus di Kawasan Kampung Tambak Mulyo Kelurahan Tanjung Mas Semarang) - Puji Restiyani; Fitriyah .; Lusia Astrika (Journal of Politic and Government Studies, 2013)
AbstractThe purpose of this study is to find out what government programs Semarang health for the poor, to analyze how the poor gain access to information on government programs and to find out semarang poor accessibility to health services, especially in the area of tambak mulyo. Based on research results this, the poor accessibility to health services carried out through several health programs are Jamkesmas and Jamkesmaskot. Lack of information about the program due to lack of socialization of government. Public access Tambak Mulyo is still difficult to obtain health care. This is illustrated through an analysis based on three indicators are used that access to health facilities, rates, and information on the village Tambak Mulyo not provide good access to health services for the cummunity.Keywords: Accessibility, The Poor, Health Service